Claves para pensar la crítica desde la filosofía de Ignacio Ellacuría - Ramírez, Fernando Lautaro (2025)
In this essay we propose to address the different methodological, epistemological and metaphysical turning points that the thought of Ignacio Ellacuría goes through, to address the critique of ideologies and the theory in charge of guiding historical praxis. This requires, first of all, showing the importance attributed to historical reality; then, examine the centrality of rational activity as a theoretical moment of total historical praxis; and, thirdly, our main concern for the hermeneutic place as a modulator of thought. Finally, we try to explain how the articulation of these aspects manages to redefine and revalue the criticism of ideologies and sociohistorical praxis.